Legal Protection for Land Grant Beneficiaries Against Revocation Efforts by Donors in Indonesian Religious Courts - Hassan, Salman; Budiono, Abdul Rachmad; Harini, Novitasari Dian Phra (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
This study aims to examine the legal basis and judicial practice regarding the revocation of land grants (hibah) by the donor and to analyze the legal protection granted to beneficiaries of land grants in the Indonesian legal system. The research employs a normative juridical method supported by a case approach, using primary legal sources such as the Compilation of Islamic Law (KHI), the Compilation of Sharia Economic Law (KHES), and the Civil Code (KUHPerdata). Three religious court decisions were analyzed: Decision No. 1175/Pdt.G/2024/PA.Smn, Decision No. 236/Pdt.G/2017/PA.Pal, and Decision No. 601/Pdt.G/2020/PA.Tnk, all of which addressed grant cancellations due to exceeding the legal limit of one-third of the donor's estate. The findings indicate discrepancies in the legal reasoning among judges. Some judges considered only the grant deed invalid while maintaining the legal status of the grant, whereas others invalidated both the grant and the deed, creating legal uncertainty for the beneficiaries. The research concludes that although a land grant is legally binding and irrevocable under normal circumstances, its legitimacy can be questioned and revoked if it violates inheritance rights or exceeds the permitted limit without the heirs' consent. The study emphasizes the need for legal harmonization and more consistent judicial interpretation to ensure legal certainty and justice for grant recipients.